2016
DOI: 10.3892/ijo.2016.3739
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gene expression profiling of ADAMs, MMPs, TIMPs, EMMPRIN, EGF-R and VEGFA in low grade meningioma

Abstract: Abstract. MMPs (matrix metalloproteinases), ADAMs (a disintegrin and metalloproteinase) and TIMPs (tissue inhibitors of metalloproteinases) are implicated in invasion and angiogenesis: both are tissue remodeling processes involving regulated proteolysis of the extracellular matrix, growth factors and their receptors. The expression of these three groups and their correlations with clinical behaviour has been reported in gliomas but a similar comprehensive study in meningiomas is lacking. In this study, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…We also identi ed the EGFR pathway as driving miR-9-1 overexpression in malignant meningioma, via FOS, which is predicted to bind to the promoter/enhancer region of miR-9-1 (43). This is in keeping with previous studies, which have shown that EGF/ERBB2 receptors and FOS are upregulated, and are involved in the molecular process that drives meningioma pathogenesis and/or progression to highergrade tumors (32,(44)(45)(46)(47)(48). FOS knock out experiments supported this observation, resulting in decreased miR-9-1 and increased E-cadherin in malignant KT21-MG1 cells (49,50).…”
Section: Discussionsupporting
confidence: 92%
“…We also identi ed the EGFR pathway as driving miR-9-1 overexpression in malignant meningioma, via FOS, which is predicted to bind to the promoter/enhancer region of miR-9-1 (43). This is in keeping with previous studies, which have shown that EGF/ERBB2 receptors and FOS are upregulated, and are involved in the molecular process that drives meningioma pathogenesis and/or progression to highergrade tumors (32,(44)(45)(46)(47)(48). FOS knock out experiments supported this observation, resulting in decreased miR-9-1 and increased E-cadherin in malignant KT21-MG1 cells (49,50).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, GO analysis revealed that the enriched ontological categories among the DEGs mainly included ECM organization, cell adhesion, angiogenesis, signal transduction and negative regulation of cell proliferation. Previous studies have revealed that matrix metalloproteinases (MMPs), which are mediators of invasion and angiogenesis, may serve important roles in the invasion and recurrence of meningioma ( 28 , 29 ). Indeed, cumulative evidence has demonstrated that the contribution of MMPs to tumor progression may be associated with the regulation of cell adhesion, the control of apoptosis via the release of factors associated with cell death or survival, and the proteolysis of the ECM ( 28 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that matrix metalloproteinases (MMPs), which are mediators of invasion and angiogenesis, may serve important roles in the invasion and recurrence of meningioma ( 28 , 29 ). Indeed, cumulative evidence has demonstrated that the contribution of MMPs to tumor progression may be associated with the regulation of cell adhesion, the control of apoptosis via the release of factors associated with cell death or survival, and the proteolysis of the ECM ( 28 , 30 , 31 ). Previous studies have demonstrated that the aforementioned GO terms are potentially important events in meningioma development and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas may invade tissue using a wide array of proteases, including matrix metalloproteinases (MMPs) and ADAMs (a disintegrin and metalloproteinase), which may be seen even in histologically benign meningiomas. 14 One study also found that up to 20% of atypical meningiomas show hypermethylation of tissue inhibitor of metalloproteinase 3 (TIMP3), encoding a protein involved in cell motility and invasion through the regulation of metalloproteinase function, which appears to be associated with aggressive behavior. 15,16 Disruption of the leptomeninges from brain invasion, surgery, and/or radiation may facilitate access of chemotactic factors and/or growth factors from tumor cells to the melanocytes residing in the leptomeninges and stimulate cell migration.…”
Section: Discussionmentioning
confidence: 99%